Peran Perencanaan Partisipatif dalam Kesiapsiagaan Bencana Gunungapi Berbasis Komunitas - Idrus, Sarifa; Hidayati, Firda; Danar, Oscar Radyan (Jurnal Ilmiah Administrasi Publik, 2022)
Understanding risks and formulating appropriate resource requirements is an important role for volcanic disaster-prone communities. However, development planners in the disaster sector often fail to understand and give a role to the community. This study aims to provide an overview of community participation in planning to support preparedness for the threat of volcanic eruptions. By using a systematic review, various related scientific sources are analyzed. The results show that participatory planning can be a forum for identifying existing conditions of threats, vulnerabilities, and community capacities and resources to minimize risks; encouraging the effectiveness of disaster preparedness policies; become a public space for the citizen to exercise their democratic rights and practice the ability to voice their interests in the implementation of disaster risk management in their area. Even though participatory planning conceptually has a good impact, it needs to be supported by the expertise of the facilitator, and adequate competence from the community and other stakeholders so that rational ideas can clash through dialogue, which is expected to produce appropriate risk reduction actions for the community.